Do elite athletes exhibit enhanced proprioceptive acuity, range and strength of knee rotation compared with non-athletes? - Muaidi, Q. I.; Nicholson, L. L.; Refshauge, K. M. (Scandinavian Journal of Medicine & Science in Sports, 2009)
The aims of this study were to compare proprioception in knee rotation in Olympic-level soccer players (N=18) with non-athletes (N=18), to explore between-limb differences in soccer players, and examine correlations between proprioception and years of playing, function, physical measures and skill level. The knee rotatory kinaesthetic device was used to present stimuli of different magnitudes to determine proprioceptive acuity for internal and external active rotation, and to measure active and passive rotation range of motion (ROM). Knee rotation strength was measured using a dynamometer. Proprioceptive acuity of the athletes was significantly (P=0.004) better than that of the non-athletes. Athletes displayed significantly less passive ROM (P=0.001), higher isometric muscle strength (P=0.006) and greater hop for distance (P=0.001) than non-athletes. No significant between-limb differences were found in the athletes in any objective outcome measure. Internal rotation proprioceptive acuity was negatively correlated with coach-rated ball skill (r=-0.52) and positively correlated with internal rotation ROM (r=0.59). Our findings suggest that highly trained athletes possess enhanced proprioceptive acuity and muscle strength that may be inherent, or may develop as a result of long-term athletic training.